Religious intertextuality in the poetry of Aisha Al-Baounia: (Al-Hadith Qudsi) as a model - Mohammed, Doha; Ali, Fatima (Al-Adab Journal, 2023)
The elimination of stylistic revelation of comments to different texts, and the revelation of discarding was known in ancient times as an investigation of the ancients but was applied in the critical field in the 1960s by Russian critics of both forms. It is the first religious authority to influence Arabic creativity in general and Sufi literature in particular. The Quran, Hadith and Sunnah of the Prophet are the most important elements of the religious traditiontheories that enriched the text, the Our research on reading Baaonic poetry is based on applying the theory of the text to her religious poetry, revealing her attachment to the Hadith as the ranking that follows the Qur ’an and affirming her poetry at various levels.